Toward an architecture of attachment disorganization: John Bowlby's published and unpublished reflections. (October 2017) - Solomon, Judith; Duschinsky, Robbie; Bakkum, Lianne; Schuengel, Carlo
This article examines the construct of disorganized attachment originally proposed by Main and Solomon, developing some new conjectures based on inspiration from a largely unknown source: John Bowlby's unpublished texts, housed at the Wellcome Trust Library Archive in London (with permission from the Bowlby family). We explore Bowlby's discussions of disorganized attachment, which he understood from the perspective of ethological theories of conflict behavior. Bowlby's reflections regarding differences among the behaviors used to code disorganized attachment will be used to explore distinctions that may underlie the structure of the current coding system. The article closes with an emphasis on the importance Bowlby placed on Popper's distinction between the context of discovery and the context of justification in developmental science.